Investigation of heritage assets essence as a category of accounting definitions - Герасименко, Ольга Миколаївна (Technology audit and production reserves, 2016)
Perfection of definitions is one of the effectiveness conditions of regulatory and legal accounting regulation and its harmonization with international accounting standards. The essence of heritage assets is investigated in accordance with international and foreign accounting standards for the public sector and expediency of implementation of this category in the terminology of accounting in Ukraine is proved. The limits of the use of «cultural heritage», «cultural values», «museum collections» terms are defined. The classification of heritage assets on different grounds is developed. Taking into account the peculiarities of the legal and regulatory framework in Ukraine, summarizing the results of scientists’ research, definition of heritage assets is proposed as a set of movable cultural property, immovable objects of cultural, natural or intangible heritage and other assets, the special features of which make it necessary to preserve, study and protect indefinitely. Implementation of the research results will allocate assets in a separate group that have common features to form accounting policy and displaying information about them in the accounting system.